Sustainable agricultural intensification and gender-biased land tenure systems: An exploration and conceptualization of interactions - Fischer, Gundula; Darkwah, A.; Kamoto, J.; Kampanje-Phiri, J.; Grabowski, P.; Djenontin, I.N.S. (Informa UK Limited, 2021)
How does sustainable agricultural intensification’s (SAI) tenet of increased productivity on the same area of land relate to prevailing gender-biased land tenure systems? How can one conceptualize the interactions between intensified land use and control over land, labour, crops and benefits – and how can equitable outcomes be facilitated? These questions (which have not yet received sufficient attention in SAI research) are explored in this study using a qualitative methodology and a gender transformative approach. Semi-structured interviews and focus group discussions with a total of 248 respondents were conducted in matrilineal and patrilineal intensification contexts in Ghana and Malawi. We develop a conceptual framework that extends Kabeer’s institutional analysis to include gender implications of SAI. Selected cases reveal how farmers and key actors link land-use intensification to existing land-related institutions with diverse outcomes. We conclude that SAI interventions should adopt gender-transformative approaches. These facilitate equitable outcomes by supporting consensus-based institutional changes and creating positive synergies between multiple scales.